Assessment of stability, adaptability and yield performance of bread wheat (Triticum aestivum l.) cultivars in south estern Ethiopia - Ayalneh, T; Letta, T.; Abinasa, M. (Plant Breeding and Seed Science, 2012)
he success of crop improvement and production activities can be enhanced with scientific information generated form genotype-environment interactions. GEI reduces the association between phenotype and genotype which result in relative ranking and stability differences of genotypes across environments. This study were conducted with the objective to identify stable, and adaptable bread wheat genotypes under various environments. Eighteen genotypes were tested across nine environments for two years on randomized block design of three replication. Plot size of 1.2 m × 2.5 m and 20cm spacing between rows were used. All recommended agronomic practices and managements were applied uniformly. Data were collected on plot basis and converted to ton ha-1. and analyzed with appropriate statistical software for stability parameters. Combined analysis over nine environments showed, variety Tuse (HAR-1407) ranked first in mean yield(3.11ton × ha-1), and K-6295-4A ranked second (3.01 ton × ha-1) and Dashen came third(2.98 ton ha-1). Analysis of AMMI model showed that the first principal component, PCA 1 explained 53.72% of the interaction sum of squares while the second principal component, PCA 2 explained 17.61% interaction sum of squares. Ecovalence(Wi) analysis showed that G2 (Sofumar(HAR-1889)), G4 (Kubsa(HAR-1685)), G5 (Tura(HAR-1407)), G7 (Galema (HAR-604)), G12 (Wabe (HAR-710)), almost equally the lowest ecovalence that evidenced less fluctuation across environment and found to be stable.